Following international trends while subject to past traditions: neuropsychological test use in the Nordic countries. (23rd December 2016) - Egeland, Jens; Løvstad, Marianne; Norup, Anne; Nybo, Taina; Persson, Bengt A.; Rivera, Diego Fernando; Schanke, Anne-Kristine; Sigurdardottir, Solrun; Arango-Lasprilla, Juan Carlos
Abstract: Objective: Historically, the neuropsychological test traditions of the four Nordic countries have spanned from the flexible and qualitative tradition of Luria-Christensen to the quantitative large battery approach of Halstead and Kløve–Matthews. This study reports current test use and discusses whether these traditions still influence attitudes toward test use and choice of tests.Method: The study is based on survey data from 702 Nordic neuropsychologists.Results: The average participant used 9 tests in a standard assessment, and 25 tests overall in their practice. Test use was moderated by nationality, competence level, practice profile, and by attitude toward test selection. Participants who chose their tests flexibly used fewer tests than those adhering to the flexible battery approach, but had fewer tests from which to choose. Testing patients with psychiatric disorders was associated with using more tests. IQ, memory, attention, and executive function were the domains with the largest utilization rate, while tests of motor, visual/spatial, and language were used by few. There is a lack of academic achievement tests. Screening tests played a minor role in specialized assessments, and symptom validity tests were seldom applied on a standard basis. Most tests were of Anglo-American origin.Conclusions : New test methods are implemented rapidly in the Nordic countries, but test selection is also characterized by the dominating position of established and much researched tests. The Halstead–Reitan and Luria traditions are currently weak, but national differences in size of test batteries seem to be influenced by these longstanding traditions.